POSITIVISME HUKUM DAN FILSAFAT MORAL : ETIKA DALAM KONTEKS HUKUM - Komang Diky Sukma Trijaya (Jurnal Komunikasi Hukum, 2025)
This paper examines the relationship between legal positivism and moral philosophy, emphasizing the role of ethics in the legal context. Legal positivism is understood as a school of thought that asserts that law should be viewed as a set of rules established by a legitimate authority, independent of underlying moral considerations or ethical values. In contrast, moral philosophy focuses on the study of the concepts of right and wrong, good and bad, and the ethical principles that govern human action. In the legal realm, fundamental questions arise regarding the extent to which moral and ethical values can, or should, influence the formation, interpretation, and application of law. This paper explores various perspectives within this debate, including the positivist perspective that positions positive law as the sole source of legal obligations, as well as the alternative view that emphasizes the importance of ethics in ensuring legal justice. Through a critical analysis of the arguments of both camps, the author seeks to find common ground between legal positivism and moral philosophy. The discussion covers the concept of universal moral principles as the normative basis of law, as well as the role of moral values in maintaining justice and the sustainability of the legal system. Furthermore, this paper highlights various challenges and dilemmas in integrating ethics into the legal positivism framework, particularly regarding the balance between individual freedom, societal interests, and legal certainty. Thus, this paper is expected to enrich legal studies through a more holistic and reflective approach.